2019
DOI: 10.1136/bmjopen-2018-025258
|View full text |Cite
|
Sign up to set email alerts
|

Time-driven activity-based costing of total knee replacements in Karachi, Pakistan

Abstract: IntroductionOsteoarthritis of the knee has been identified as the most common disability in Pakistan. Total knee replacement (TKR) surgery is the curative treatment for advanced osteoarthritis of the knee; however, cost remains one of the barriers to effective and timely service delivery.ObjectiveWe conducted a time-driven activity-based costing (TDABC) analysis of TKR to identify major cost drivers and areas for process improvement.Methods and analysisWe performed a prospective TDABC analysis of patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Step 7 is to calculate the total cost of patient care. Several studies have addressed elements of applying TDABC to the total joint arthroplasty arena 12-17 . Step 2 is often one of the most difficult steps to accomplish, as it can be difficult to garner institutional resources and buy-in to create a comprehensive care delivery value chain (CDVC) model.…”
Section: Discussionmentioning
confidence: 99%
“…Step 7 is to calculate the total cost of patient care. Several studies have addressed elements of applying TDABC to the total joint arthroplasty arena 12-17 . Step 2 is often one of the most difficult steps to accomplish, as it can be difficult to garner institutional resources and buy-in to create a comprehensive care delivery value chain (CDVC) model.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,12,16 Some used this general calculation for costs such as administration and insurance, but space and electricity were calculated based on specific consumption for each process. 15 Akhavan et al calculated these indirect costs based on their consumption for each activity, estimating how many full-time equivalent employees were associated with each activity (from human resources, finance, and IT). 3 The majority of indirect costs in these studies were calculated as a fraction of the general overhead found in most hospital databases.…”
Section: Indirect Costsmentioning
confidence: 99%
“…Pre-procedure, procedure, and post-procedure phases were observed as described in previous studies. 17,20,21 At the pre-procedure phase, patients are admitted and prepared for the procedure at the haemodynamic unit; the procedure phase is substantially performed by physicians with the support of nurses and nurse technicians at the haemodynamic unit; and the post-procedure phases include the period of patient recovery after ICP in the haemodynamic unit before transfer to another unit. Different variables were selected for evaluation personnel, corporate and divisional allocations (hospital structure), and medications and materials related to each procedure phase.…”
Section: Data Collectionmentioning
confidence: 99%